FRI0168 Restoration of decreased lymphocytes, CD8+T cell subsets with TH1 skewed phenotype associate with spontaneous regression of lympho-proliferative disorders in rheumatoid arthritis patients treated with methotrexate. (15th June 2017) - Saito, S; Suzuki, K; Yamaoka, K; Amano, K; Tokuhira, M; Takeuchi, T
Abstract : Background: Lympho-proliferative disorder (LPD) is known as a relatively rare but life-threatening complication in RA patients under MTX administration. Spontaneous regression of LPD after MTX withdrawal is regarded as a distinct character of LPD under MTX administration. Previous study from our institution [1] and others [2] reported the link between decreased lymphocyte counts at LPD diagnosis and restoration after MTX cessation and the regression of LPD. Objectives: To investigate the immunological factors including lymphocyte subsets which involved in spontaneous regression of LPD following MTX withdrawal. Methods: We studied 35 RA patients complicated with LPD under MTX administration in our institution. Age, sex, RA disease duration matched control MTX-treated patients (N=35) were selected. LPD patients were divided into two groups regarding to the status of LPD after MTX cessation; regressive group (N=22) and persistent group (N=13). Clinical features were compared among 3 groups. Flowcytometric analysis of the whole blood sample and measurement of cytokine concentration in ELISA were conducted in a part of the LPD patients (N=10, 7 regressive, and 3 persistent LPD) and controls (N=10). The time of MTX cessation, which was simultaneous with LPD diagnosis, was defined as week 0, and blood sample was collected at week 0, 4 and 12. Results: At week 0, number of peripheral lymphocytes was significantly decreased in regressive group, compared to persistent group and control group. Flowcytometric analysis revealed significant decrease in proportion of effector memory CD8+ T cells (EMCD8+T), Epstein Barr Virus specific CD8+ T cells (EBV specific CD8+) and T helper 1 cells (Th1 cells) subset in regressive group compared to control group. Following MTX cessation, significant increase in proportion and absolute number of these subsets were observed only in the regressive group, but not in persistent group. Expansion of Th1 cells and EMCD8+ T cells significantly correlated with increase of serum IFN-γ, and expansion of EMCD8+ T cells inversely correlated with change of serum IL-15. Conclusions: Restoration in proportion and absolute number of Th1 cells, EMCD8+T cells and EBV specific CD8+ T cells coincided with increase of IFN-γ, and associated with regression of LPD developed under MTX administration. Since changes of those immunological factors were not observed in persistent LPD, this study would be the first report to demonstrate the difference of immune status between regressive and persistent LPDs developed under MTX administration. References: Saito S, et al. Rheumatology. 2017; in press. Inui Y, et al. Leuk Lymphoma. 2015; 56(11):3045–3051. Acknowledgements: None. Disclosure of Interest: S. Saito: None declared, K. Suzuki: None declared, K. Yamaoka Speakers bureau: Pfizer, Chugai Pharma, Mitsubishi-Tanabe Pharma, Takeda Industrial Pharma, GlaxoSmithKline, Nippon Shinyaku, Eli Lilly, Janssen Pharma, Eisai Pharma, Astellas Pharma and Actelion Pharmaceuticals, K. Amano: None declared, M. Tokuhira Speakers bureau: Eisai Co., T. Takeuchi Grant/research support from: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, 2, Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K.,